The Three Stooges collection. Volume two, 1937-1939 [videorecording (DVD)]. - Howard, Moe; Howard, Jerome Lester, 1903-1952; Fine, Larry (Three Stooges., 2016)
"Get ready for more outrageous antics as The Three Stooges return in this second collection of chronological masterpieces. These 24 shorts, filmed from 1937-1939, are digitally remastered for the highest quality - every sight, gag and knuckle-cracking sound can be seen and heard with the utmost clarity for maximum effect. This period is considered to be when Larry, Moe, and Curly hit their stride and perfected their craft, when all the elements came together perfectly: the writing, directing, pacing, and performances. It's no wonder The Stooges made some of their best films during this period, proving laughter really is the best medicine in such classics as Dizzy Doctors, Saved By The Belle, and Calling All Curs."--Jbhifi.com.au.